2019
DOI: 10.3389/fevo.2019.00161
|View full text |Cite
|
Sign up to set email alerts
|

Non-native Mammals Are the Main Seed Dispersers of the Ancient Mediterranean Palm Chamaerops humilis L. in the Balearic Islands: Rescuers of a Lost Seed Dispersal Service?

Abstract: Muñoz-Gallego et al. Chamaerops Humilis Seed-Dispersal Rescuers martens. We conclude that these two non-native mammal species are effective seed dispersers of C. humilis in this and probably other Mediterranean islands, where humans led to the extinction of its native seed dispersers, as it was probably the case of the goat-like Myotragus balearicus in the Balearic Islands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 102 publications
1
36
0
Order By: Relevance
“…For instance, when fox losses were completely compensated with badgers, seed dispersal into Mediterranean scrubland increased to a level that even surpassed the baseline scenario. Similar compensation has been documented not only among native seed dispersers (Cordeiro andHowe 2003, Zhou et al 2013) but also by introduced and domestic species (García et al 2014, Cares et al 2018, Muñoz-Gallego et al 2019. However, such apparent compensation could be less complete if disperser species differ in subtle but key aspects of the seed dispersal process (e.g.…”
Section: The Effects Of Defaunation and Density Compensation On Seed supporting
confidence: 58%
“…For instance, when fox losses were completely compensated with badgers, seed dispersal into Mediterranean scrubland increased to a level that even surpassed the baseline scenario. Similar compensation has been documented not only among native seed dispersers (Cordeiro andHowe 2003, Zhou et al 2013) but also by introduced and domestic species (García et al 2014, Cares et al 2018, Muñoz-Gallego et al 2019. However, such apparent compensation could be less complete if disperser species differ in subtle but key aspects of the seed dispersal process (e.g.…”
Section: The Effects Of Defaunation and Density Compensation On Seed supporting
confidence: 58%
“…A recent analysis of 74 tropical/subtropical islands found that extinctions of frugivores have resulted in a body mass decrease of 37% globally, and in some cases, native frugivores on islands have been completed extirpated 54 . However, it remains to be seen how effectively nonnative (alien) frugivores are compensating for the seed dispersal function provided by lost native frugivores 58 , and how plant-frugivore networks will rewire given novel communities caused by climate change, translocations, and (re)introductions 59,60 . Some evidence already shows that nonnative frugivores may actually promote the dispersal of nonnative plant species more effectively than that of native plants 57 , suggesting that ecosystem outcomes may be context-specific.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in some cases, these alien species may be the only available partners acting as “rescuers” of mutualistic interactions and the derived ecosystem functions (Foster and Robinson ; Muñoz‐Gallego et al. ), despite having an overall negative effect on the native community by, for instance, enhancing further invasions (e.g., Kawakami et al. ; Pejchar ; Wotton and McAlpine ; MacFarlane et al.…”
mentioning
confidence: 99%
“…In some cases, alien species act as beneficial partners of native species, and to some extent can be functionally adequate replacements of native counterparts (Kawakami et al 2009;Burns 2012;García et al 2014;Pejchar 2015). In fact, in some cases, these alien species may be the only available partners acting as "rescuers" of mutualistic interactions and the derived ecosystem functions (Foster and Robinson 2007;Muñoz-Gallego et al 2019), despite having an overall negative effect on the native community by, for instance, enhancing further invasions (e.g., Kawakami et al 2009;Pejchar 2015;Wotton and McAlpine 2015;MacFarlane et al 2016;Kaushik et al 2018).…”
mentioning
confidence: 99%